Language Mediation as Communication System. Issue 4 (11th May 2017) - Baraldi, Claudio
Abstract: Language mediation is employed as a possible solution for problems of migrants' inclusion in institutional services, within multilingual and multicultural societies. Interpreting Studies has highlighted that language mediation is coordination of social interactions and social construction of narratives. This paper explains language mediation using Luhmann's theory of communication systems, in particular the concepts of self-reference, reflexivity, function, structure, and structural coupling. Language mediation is observed as a self-referential communication system fulfilling the function of promoting participation and new narratives through reflexive coordination. In particular, the concept of structural coupling explains how language mediation can enhance change within other communication systems, promoting dialogue across difference. Language mediation, however, can also assume a hierarchical structure, which creates marginalization and ethnocentrism.